1982
DOI: 10.1111/j.1365-2125.1982.tb01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of labetalol with other anti‐hypertensive drugs.

Abstract: 1 The anti‐hypertensive effects of labetalol have been compared and contrasted with other groups of anti‐hypertensive drugs in this review of the published literature. 2 The data show that the pharmacological and haemodynamic profile of labetalol in man is distinctly different from that of other specific anti‐hypertensive agents; namely the properties of competitive alpha‐and beta‐adrenoceptor blockade leading to haemodynamic effects of reduced blood pressure and peripheral vascular resistance with little acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…These various studies generally confirm the consensus of earlier reports showing that blood pressure reduction is mainly due to reduced peripheral resistance, with little accompanying change in resting heart rate or cardiac output (Prichard & Richards, 1982). Significant lowering of plasma renin and aldosterone was also confirmed (Fagard et al, 1982).…”
Section: Clinical Pharmacologysupporting
confidence: 88%
See 1 more Smart Citation
“…These various studies generally confirm the consensus of earlier reports showing that blood pressure reduction is mainly due to reduced peripheral resistance, with little accompanying change in resting heart rate or cardiac output (Prichard & Richards, 1982). Significant lowering of plasma renin and aldosterone was also confirmed (Fagard et al, 1982).…”
Section: Clinical Pharmacologysupporting
confidence: 88%
“…Cardiac output was not significantly altered in these acute studies. Cohn et al (1982) (Prichard & Richards, 1982). Significant lowering of plasma renin and aldosterone was also confirmed (Fagard et al, 1982).…”
Section: Clinical Pharmacologymentioning
confidence: 88%
“…Labetalol, in both fixed and individually titrated doses, has been used outside the United States since 1975 for the management of mild, moderate, and severe hypertension [52][53][54][55]. A number of investigators using labetalol have reported the drug to be at least as effective in lowering blood pressure as a wide range of other antihypertensive drugs.…”
Section: Essential Hypertenisonmentioning
confidence: 99%
“…Multiple reports identify the nature and frequency of side effects with labetalol [1,54,68,75,89,90]. Side effects are generally mild and self-limited.…”
Section: Side Effects and Contraindicationsmentioning
confidence: 99%
“…Earlier studies did not find the antihypertensive effect of combined //β‐blockade with labetalol to be significantly greater than that of β‐blocker monotherapy 15 . However, labetalol is lipophilic and subject to considerable first‐pass hepatic metabolism, with low bioavailability in the range of 25% to 33%, and with considerable interindividual variation in bioavailability 16,17 .…”
Section: Reasons For Underuse Of Combined α/β‐Blockadementioning
confidence: 95%